The Role of Aqidah Akhlak Instruction in Instilling Character Values Among Madrasah Students - Sayidah, Aminatus; Fatimah, Meti (Abjadia : International Journal of Education, 2025)
This study aims to examine the role of the Aqidah Akhlak subject as an effective medium in instilling character values in students in madrasas. Amidst the moral crisis that is hitting the younger generation, character education has become a major focus in the national education system. As an integral part of Islamic education, Aqidah Akhlak learning has a strategic position in shaping the character of students who are faithful, honest, tolerant, and have noble character. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results show that Aqidah Akhlak learning is effective in internalising character values through the integration of faith material with students' daily practices. Values such as honesty, trustworthiness, responsibility, discipline, as well as politeness and respect for teachers and parents are successfully instilled through teacher role models, habituation, and contextual learning. However, challenges were also found, such as less-than-optimal learning strategies, the negative influence of digital media, and weak control in the application of values outside the madrasah environment. Thus, it is necessary to strengthen the curriculum, innovate methodology, and increase the role of teachers as character facilitators in facing the challenges of the times. Keywords: Aqidah Akhlak, media, character values, students